Making of the Goose Skeleton by Washing Method - Haleem, Khatera; Hamid , Asadullah (Journal of Natural Sciences – Kabul University, 2021)
The goose is a loyal, intelligent, and beautiful domestic bird with social and economic importance. Goose eggs are rich in proteins and vitamins, with protein levels significantly higher than chicken eggs. The skeleton of a goose, similar to other domestic birds and mammals, consists of the skull, keel (sternum), forelimbs (wings), and hind limbs (legs). Preparing animal and bird skeletons is a vital routine activity in veterinary anatomy laboratories. Goose skeletons are valuable for teaching, learning, and conducting various individual and comparative research studies. This study details the preparation of a goose skeleton using the washing method, a significant achievement for the Department of Veterinary Anatomy and the Faculty of Veterinary Science at Kabul University.